PENGELOLAAN DAN PEMANFAATAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT - Zarkasi, A (JISIP UNJA (Jurnal Ilmu Sosial Ilmu Politik Universitas Jambi), 2018)
This research looks at how the development of village funds management in empowering rural communities and in the administration of government and village development. The Village Fund can be used for financing community empowerment programs. Considering Indonesian citizens still live in rural areas. The use of village funds should be applicable in the fields of education, health, physical development and increasing the resilience of villagers, including village innovation programs, which aim to alleviate poverty, renew inter-villages and empower the community's economy. The findings in this study are the implementation of community empowerment in accordance with the use of village funds which are made according to the first priority. The Village Fund is used for the welfare of the community and its management in a transparent and accountable manner.